Bilateral Congenital Cataract Associated with Multiple Epiphyseal Dysplasia: A case Report - Adhikari, S; Shrestha, U; Nepal, P; Singh, JL (Journal of Nepal Paediatric Society, 2012)
Cataract in children has varied etiology. It may be associated with systemic diseases including skeletal dysplasias. However cataract in Multiple Epiphyseal Dysplasia is a rare association. A child presented with bilateral dense posterior sub capsular cataract and multiple bony abnormalities. Clinical and radiographic findings suggested the disease to be Multiple Epiphyseal Dysplasia. The aim of presenting this case is to report a case of congenital cataract having a rare association with the Multipe Epiphyseal Dyspalsia. Key words: Congenital cataract; Multiple Epiphyseal Dysplasia; Skeletal dysplasia DOI: http://dx.doi.org/10.3126/jnps.v32i1.5434 J. Nepal Paediatr. Soc. Vol.32(1) 2012 71-72